2010
DOI: 10.1097/ccm.0b013e3181b78fa8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic outcomes of the electronic intensive care unit: Results from two community hospitals*

Abstract: In our study of >4000 patients representing two community hospitals, we did not find a reduction in mortality, length of stay, or hospital cost attributable to the introduction of the eICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 14 publications
2
92
0
Order By: Relevance
“…28,34 Only two (11%) studies and expansion seems likely. 7 Despite rapid adoption, reported effectiveness of tele-ICU coverage has varied across studies, [8][9][10][11] and studies often have neglected to address tele-ICU impact on staff. Staff impact is important as evidenced by a report of one hospital system that dropped tele-ICU coverage after 2 years.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…28,34 Only two (11%) studies and expansion seems likely. 7 Despite rapid adoption, reported effectiveness of tele-ICU coverage has varied across studies, [8][9][10][11] and studies often have neglected to address tele-ICU impact on staff. Staff impact is important as evidenced by a report of one hospital system that dropped tele-ICU coverage after 2 years.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] Because each study was missing one or more important data elements (e-Appendix 2), we contacted the authors of each study in an effort to obtain additional data; all but two of the authors responded, but none were able to provide additional data.…”
Section: For Editorial Comment See Pagementioning
confidence: 99%
“…Six studies presented data concerning the impact of tele-ICUs on hospital variable costs ( Table 3 ). [23][24][25][28][29][30] After tele-ICU implementation, studies with vendor affi liation reported a cost savings of $2,600 to $3,000 per patient and suggested that tele-ICUs increased hospital profi ts by $1,000 to $4,000 per patient. 23,25,28 Studies without vendor affi liation reported no variable cost savings and suggested increased hospital costs after implementation.…”
Section: Tele-icu Costsmentioning
confidence: 99%
See 2 more Smart Citations